Some high Sounding Balloon Ascents and Upper Air Temperatures upto 35 km over India (MAUSAM, 1952)
Data from 34 sounding balloon ascents over India reaching 30 km and above have been collected and the seasonal mean temperatures derived from them are briefly discussed. Temperatures at 30 and 35 km shown by these data, of the order of 220° to 230 ° A, have been compared and found to agree reasonably well with temperatures at same heights over similar latitudes in other parts of the world. It is shown that Koteswaram's estimates of temperatures over Central India at these heights are very high and that up to 36 kill the sounding balloon data do not show any large increase of temperature with height above 25 kill. Using means of sounding balloon data over 9 stations in India up to 1940, a diagram showing the distribution of upper air temperatures over India up to 35 km in summer and winter has been drawn. and presented. The chief features of the variation of the height and temperature of tropopause and of the lapse rate, the annual range and the horizontal gradient of temperature have been stated and briefly discussed. The outstanding points which emerge from the study a~~(i) The summer tropopause over India is higher and cooler than the winter tropopause. The transition from the tropical type to the polar type stratosphere to be occurs at 30°N in winter and at latitudes north of India in summer; (ii) Maximum lapse rates in the troposphere up to 30°N occur at 12-14 km in summer and 9-11 km in winter. The region of high lapse rates shows a variation similar to the height of tropopause ; (iii) In the lower stratosphere, counter-lapse rates increase with height above the tropopause up to 19-21 kill after which they decrease. The counter lapse rates are generally higher. in summer than in winter. Above 25 km, the counter-lapse rates are of the order of 0.5 to 1°C per kilometre ; (iv) Summer temperatures are higher than winter temperature  up to 14 km above which the reverse happens up to 20 km. Above 20 km again the summer temperatures are higher than winter temperatures. The annual range of temperature is maximum at 8 to 10 km and decreases rapidly thereafter with ,height. The range is large over North India and very small over South India and1l') In the, troposphere, the horizontal gradient of temperature is positive in summer except between 4 and 11 km north of latitude 27°N where it is negative. In winter, it is negative below 11 to 12 km and positive above. The temperature gradient is rather small south of latitude 15°N. In the lower stratosphere between 16 and 20 km, it is positive and steep in the lower latitudes south of 13°N and decreases with latitude north of it.